A Novel Vascular Endothelial Growth Factor Receptor Participates in White Spot Syndrome Virus Infection in Litopenaeus vannamei - Li, Shihao; Wang, Zhiwei; Li, Fuhua; Yu, Kuijie; Xiang, Jianhai (Frontiers in Immunology, 2017)
Vascular endothelial growth factor (VEGF) is signaling pathway known to play key roles in endothelial cell proliferation, migration, angiogenesis, vascular permeability, inhibition of apoptosis and virus infection. In the present study, a novel VEGFR gene (LvVEGFR2) was identified and characterized from Litopenaeus vannamei. The deduced amino acid sequence of LvVEGFR2 possessed typical features of VEGFRs reported in other species, including six IG-like domains, a trans-membrane domain, a protein kinase domain and one tyrosine-protein kinase active site. The transcripts of LvVEGFR2 were mainly detected in hemocytes and lymphoid organ (Oka). Subcellular localization analysis showed that LvVEGFR2 was a membrane protein. Its expression level was obviously up-regulated in hemocytes and Oka of the shrimp after WSSV infection. Knock-down of LvVEGFR2 gene expression by double-strand RNA mediated interference could lead to a decrease of virus copy number in WSSV infected shrimp. The interaction between LvVEGFR2 and different LvVEGFs (LvVEGF1, LvVEGF2 and LvVEGF3) in shrimp was analyzed at the transcription level and protein level, respectively. Knockdown of LvVEGF2 or LvVEGF3 could down-regulate the expression level of LvVEGFR2, and injection of the recombinant LvVEGF2 or LvVEGF3 could up-regulate the expression level of LvVEGFR2. Yeast two-hybrid analysis showed that LvVEGFR2 could interact with LvVEGF2 and LvVEGF3 directly. The study improved our understanding on the VEGF signaling pathway of shrimp and its role during WSSV infection.